Evaluation of the Simultaneous Election System and Its Impact on the Quality of Democracy in Indonesia - Dewa Erlangga; Ganca Saputra; Aghisna Syakira bilbina; Rudi Santoso (CV. Dyoqu Publishing and Management, 2026)
Background: Indonesia’s simultaneous election system was implemented to improve governmental efficiency, strengthen political consolidation, and enhance democratic accountability. However, its implementation has also generated various challenges related to electoral management, voter behavior, and institutional performance. Aims: This study aims to evaluate the implementation of the simultaneous election system in Indonesia and analyze its impact on the quality of democracy, particularly in terms of political participation, electoral effectiveness, and democratic representation. Methods: This research employs a qualitative descriptive approach using literature review methods. Data were collected from academic journals, government reports, election regulations, and previous studies related to Indonesia’s electoral system and democratic development. Result: The findings indicate that simultaneous elections have contributed to increased voter participation and strengthened the efficiency of the electoral process. Nevertheless, the system has also created administrative burdens, increased political polarization, and reduced the quality of voter consideration due to the complexity of multiple ballots conducted at the same time. These conditions affect the effectiveness of democratic representation and electoral integrity. Conclusion: The simultaneous election system in Indonesia provides both opportunities and challenges for democratic quality. Improvements in electoral management, voter education, and institutional capacity are necessary to ensure that the system can support a more effective, inclusive, and substantive democracy.